Functional Characterization of the Effects of N-acetyltransferase 2 Alleles on N-acetylation of Eight Drugs and Worldwide Distribution of Substrate-Specific Diversity - Fukunaga, Koya; Kato, Ken; Okusaka, Takuji; Saito, Takeo; Ikeda, Masashi; Yoshida, Teruhiko; Zembutsu, Hitoshi; Iwata, Nakao; Mushiroda, Taisei (Frontiers in Genetics, 2021)
Variability in the enzymatic activity of N-acetyltransferase 2 (NAT2) is an important contributor to interindividual differences in drug responses. However, there is little information on functional differences in N-acetylation activities according to NAT2 phenotypes, i.e., rapid, intermediate, slow, and ultra-slow acetylators, between different substrate drugs. Here, we estimated NAT2 genotypes in 990 Japanese individuals and compared the frequencies of different genotypes with those of different populations. We then calculated in vitro kinetic parameters of four NAT2 alleles (NAT2*4, *5, *6, and *7) for N-acetylation of aminoglutethimide, diaminodiphenyl sulfone, hydralazine, isoniazid, phenelzine, procaineamide, sulfamethazine (SMZ), and sulfapyrizine. NAT2*5, *6, and *7 exhibited significantly reduced N-acetylation activities with lower Vmax and CLint values of all drugs when compared with NAT2*4. Hierarchical clustering analysis revealed that 10 NAT2 genotypes were categorized into three or four clusters. According to the results of in vitro metabolic experiments using SMZ as a substrate, the frequencies of ultra-slow acetylators were calculated to be 29.05–54.27% in Europeans, Africans, and South East Asians, whereas Japanese and East Asian populations showed lower frequencies (4.75% and 11.11%, respectively). Our findings will be helpful for prediction of responses to drugs primarily metabolized by NAT2.